Dim and bright void regimes in capacitively-coupled RF complex plasmas. (24th March 2021) - Pikalev, A; Semenov, I; Pustylnik, M; Räth, C; Thomas, H
Abstract: We demonstrate experimentally that the void in capacitively-coupled RF complex plasmas can exist in two qualitatively different regimes. The 'bright' void is characterized by bright plasma emission associated with the void, whereas the 'dim' void possesses no detectable emission feature. The transition from the dim to the bright regime occurs with an increase of the discharge power and has a discontinuous character. The discontinuity is manifested by a kink in the void size power dependencies. We reproduce the bright void (mechanically stabilized due to the balance of ion drag and electrostatic forces) by a simplified time-averaged 1D fluid model. To reproduce the dim void, we artificially include the radial ion diffusion into the continuity equation for ions, which allows to mechanically stabilize the void boundary due to very weak electrostatic forces. The electric field at the void boundary occurs to be so small that it, in accordance with the experimental observation, causes no void-related emission feature.